Auditory Processing of Gender Agreement across Relative Clauses by Spanish Heritage Speakers - Daniel Vergara; Gilda Socarrás (Languages, 2020)
Processing research on Spanish gender agreement has focused on L2 learners’ and—to a lesser extent—heritage speakers’ sensitivity to gender agreement violations. This research has been mostly carried out in the written modality, which places heritage speakers at a disadvantage as they are more frequently exposed to Spanish auditorily. This study contributes to the understanding of the differences between heritage and L2 grammars by examining the processing of gender agreement in the auditory modality and its impact on comprehension. Twenty Spanish heritage speakers and 20 intermediate L2 learners listened to stimuli containing two nouns with gender mismatches in the main clause, and an adjective in the relative clause that only agreed in gender with one of the nouns. We measured noun-adjective agreement accuracy through participants’ responses to an auditory task. Our results show that heritage speakers are more accurate than L2 learners in the auditory processing of gender agreement information for comprehension. Additionally, heritage speakers’ accuracy is modulated by their Spanish language proficiency and age of onset. Participants also exhibit higher accuracies in cases in which the adjective agrees with the first noun. We argue that this is an ambiguity resolution strategy influenced by the experimental task.